Reconstruction of Maqashid al-Shariah Thought in Islamic Intellectual History and Its Relevance to the Development of Contemporary Islamic Law - Muhammad Amar Adly; Sofwan Tambunan; Zaini Munawir; Ahmad Senang (ISNU Nine-Star Multidisciplinary Journal, 2026)
The development of modern society presents a variety of increasingly complex legal issues that are often not explicitly discussed in classical Islamic jurisprudence literature. This condition creates the need for a methodological approach capable of bridging the gap between normative Islamic texts and the ever-evolving social dynamics. In this context, the concept of maqasid al-shari'ah becomes an important approach in the development of Islamic legal ijtihad oriented towards the benefit of Allah. This study aims to analyze the development of maqasid al-shari'ah thought in Islamic intellectual history and examine its relevance in the development of contemporary Islamic law. This study uses a qualitative approach with library research methods and historical analysis of the development of the maqasid concept in classical and modern literature. The research data were obtained through a review of the works of ulama usul fiqh as well as the thoughts of contemporary scholars who discuss maqasid theory and its application in Islamic legal methodology. The results show that the concept of maqasid al-shari'ah has undergone significant development in the history of Islamic thought, starting from its initial formulation regarding the benefit in the classical usul fiqh tradition to its broader reinterpretation in modern Islamic thought. These developments demonstrate that maqasid functions not only as a theoretical concept in Islamic legal studies but also as a methodological paradigm that allows Islamic law to adapt to social change without abandoning the fundamental principles of sharia. This study concludes that the maqasid approach has strong relevance in addressing various modern legal problems because it provides a more substantive and contextual interpretative framework. Therefore, the development of maqasid studies needs to continue through an interdisciplinary approach to strengthen the ijtihad methodology and enhance the contribution of Islamic law in addressing legal challenges in the modern era.